Book Review of Dreamland: The True Tale of America's Opiate Epidemic - Shannon M. Monnat (Journal of Research in Rural Education, 2016)
To say that the United States is in the midst of an opiate epidemic seems cliché at this point. In 2014, there were nearly 30,000 deaths related to prescription painkillers and heroin, representing a four-fold increase since 1999 (National Institute on Drug Abuse, 2015). Over the past two years, thousands of media articles have been written about it, numerous television and radio news sources have run profi les on addicts, nearly all U.S. states and counties have held public hearings, Congress passed new laws, and President Obama pledged funding and action to address the crisis. Especially newsworthy has been the "surprising" demographics of new opiate users (Whites, middle-aged women, teenagers from "good families"). Moreover, whereas heroin use was once concentrated in major coastal cities, its availability, use, and overdose rates have swelled in smaller interior cities, towns, and rural hinterlands.